Comparison of dimensional changes of two cold- cured acrylic resins: Acropars and Meliodent - Ebadian B. Assistant Professor; Bazargan Zadeh MA. Dentist (Tehran University of Medical Sciences, 2003)
Statement of Problem: The construction of dental materials has been developing inside the country."nCold- cured acrylic resins are of such materials which are used in removable prostheses."nPurpose: The aim of this study was to compare the dimensional changes of two types of cold-cured"nacrylic resins, Acropars and Meliodent."nMaterial and Methods: Forty acrylic discs, with diameter of 13.7 mm, were made of Acropars and"nMeliodent acrylic resins (20 samples in each group). Then, each group was randomly divided into two"nparts. The first group was kept in usual environment, whereas the samples of the second group were"nplaced in the boiling water for five minutes. The dimensional changes of the samples, at different"nintervals and seven days post curing, were measured by light microscope and recorded. Variance analysis"nwas used to analyze the results."nResults: Acropars resins, comparing to Meliodent ones, showed a considerable dimensional changes,"nwhich was statistically significant. Boiling of Acropars resins, for five minutes, lead to a significant"nshrinkage. The maximum shrinkage occured at 24 hours post curing."nConclusion: If the tray is made of Acropars acrylic resin, it is recommended to take impression, 24 hours"nafter its setting.